Examining Black and Latinx STEM graduate students’ laboratory rotation experiences and their impact on advisor selection - Bryson, Tasia; Grunert Kowalske, Megan; Wilkins-Yel, Kerrie; Adineh, Shadi (Frontiers in Education, 2024)
Despite being fundamental to graduate education in the sciences, lab rotations are largely unexplored in the academic literature. The purpose of this study is to understand how the laboratory rotation process impacts Black and Latinx STEM graduate students' advisor selection process. Steeped in Critical Race Theory, this study employed a case study approach to explore the experiences of four Black and Latinx STEM graduate students enrolled at Predominantly White Institutions (PWIs). The findings suggest that students who participated in lab rotations were able to gain more insights into their advisor's advising style and lab environment before making their decision. Participants felt more comfortable in labs where the advisors provided a hands-on advising style over a hands-off advising style. Ultimately, results indicated that Black and Latinx STEM graduate students benefited from participating in lab rotations prior to selecting their research advisors. This study's findings may help STEM departments, especially those within PWIs, understand the importance of consistently offering lab rotations for Black and Latinx STEM graduates prior to selecting their graduate advisor.